Suicidal ideation and their relationship with job satisfaction and job strain among Jordanian hospitals’ healthcare professionals: a cross-sectional study - Alnajdawi, Ann Mousa; Alsawalqa, Rula Odeh; Alrawashdeh, Maissa N. (Frontiers in Public Health, 2024)
Suicidal ideation is a major health problem that occurs in response to complex interactions among psychological, sociocultural, and environmental factors. The phenomenon of suicidal ideation among healthcare professionals is still shrouded in mystery in Jordanian society, and there is still a scarcity of studies on its relationship with job strain and job satisfaction has been examined in the Arab world. Therefore, to fill this gap, this study aimed to reveal the prevalence of suicidal ideation among Jordanian hospitals health care professionals, and its relationship to job satisfaction and job strain. Additionally, how some sociodemographic factors were correlated with suicidal ideation levels, including age, sex, monthly income, occupation, years of experience, and sector type. Data were collected through a survey including sociodemographic characteristics, Suicidal ideation Scale (SIS), Job Satisfaction Survey (JSS), and Demand Control Support Questionnaire (DCSQ). The survey was distributed among 910 physicians and nurses of both sexes in public and private Jordanian hospitals. The survey was conducted using an anonymous online platform via Google Forms between October 2022 and December 2023. In light of the strain theory of suicide (STS), our results showed that physicians and nurses reported low levels of suicidal ideation and job satisfaction, with high levels of job strain. Suicidal ideation was positively correlated with job strain and negatively correlated with job satisfaction. Job satisfaction is negatively correlated with job strain. Job satisfaction was a significant mediator between job strain and suicidal ideation. Greater attention should be paid to the work environment in healthcare, particularly to enhance social support, increase job satisfaction levels, reduce job strain, and provide extensive training on effective prevention strategies for suicidal ideation and behaviour in the workplace. Additionally, policies and practices related to the health sector should be modified to create stable, healthy, and safe relationships and work environments.